Neonatal and Maternal Postpartum Bacteroides Bacteremia - Nahid Zaker; Joy Lertzman; Joanne Embree (Canadian Journal of Infectious Diseases)
OBJECTIVE: A unique case of Bacteroides fragilis bacteremia in a mother and her infant prompted a review of these infections in neonates and postpartum mothers during a five-year period at two institutions in Winnipeg, Manitoba. The purpose was to determine the frequency of these infections and ascertain commonly associated factors.